Smart Water Management Framework Berbasis IoT Untuk Mendukung Pertanian Urban - Yan Mitha Djaksana; Heru Sukoco; Sri Wahjuni; Hendra Rahmawan; Shelvie Nidya Neyman (PETIR, 2021)
Related to water resources is one of the problems that often occurs in certain areas that have large populations such as urban areas, in addition to having to provide water that is used for daily activities, today many urban residents live in urban hardships, so an alternative is needed in providing resources water that must be purchased in daily necessities, in this paper we proposed a framework for support urban farming that we called the smart water management system by utilizing the IoT (Internet of Thinks) technology specifically sensors and machine learning algorithms in managing available water resources. many researchers have developed a similar model, but the framework model that we proposed using reuse water and filtered rainwater so that it meets the minimum quality requirements of water that can be reused in agriculture, so we hopes to make domestic water use more effective and efficient and predictable water consumption and availability.